An investigation of source use strategies in published research articles and graduate students research papers - Mansourizadeh, K. (Asian EFL Journal Press, 2016)
Integrating source texts appropriately and effectively from various sources into ones own writing poses significant challenges for student writers as it demands sophisticated advanced academic skills. Beginning writers could benefit from studying strategies employed by more established writers from the same field. This paper reports the results of an investigation of source use strategies employed in 6 published research articles and 6 unpublished masters student papers from the field of chemical engineering. Different source use strategies were categorized as paraphrase, summary, generalization and exact copying. The findings demonstrated that while in research articles, summaries and generalizations were frequently employed, in students papers, paraphrases were used the most. The results also showed that the frequency of extensive citations was much higher in students papers and in many instances the student writers were too dependent on the source texts. Interviews with the student writers revealed gaps in their knowledge of acceptable source use while the expert informants credited their competence to practice, experience, and knowledge of the field.